Making the Case for an English Academy: Reflections on an Ongoing Endeavor - Geoff Bender (Educational Considerations, 2020)
This article makes a case for the academy as a site for meaningful school-university dialogue in order to strengthen rapport across stakeholders in the teacher education process while generating crucial data for a teacher education program’s continuous improvement. Similar in some ways to its cousins, including the leadership academy and the professional development school, the academy model described here is distinguished from these related structures in its diverging purposes. While invested in bringing new professionals into the field, the English Academy keeps its linked teacher education program abreast of trends in public education that help shape that program’s work in preparing future teachers. Just as important, however, is the academy’s emphasis on syncretized understanding: stakeholders interweave perspectives of the field through productive conversation to yield a heightened view of each stakeholder’s work, stresses, and accomplishments. The result is mutually educative and a crucial strengthening of bonds in one growing school-university partnership.
Keywords: professional development; teacher education; school-university partnerships